2012
DOI: 10.3390/rs4113462
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Savanna Tree Species at Ecosystem Scales Using Support Vector Machine Classification and BRDF Correction on Airborne Hyperspectral and LiDAR Data

Abstract: Abstract:Mapping the spatial distribution of plant species in savannas provides insight into the roles of competition, fire, herbivory, soils and climate in maintaining the biodiversity of these ecosystems. This study focuses on the challenges facing large-scale species mapping using a fusion of Light Detection and Ranging (LiDAR) and hyperspectral imagery. Here we build upon previous work on airborne species detection by using a two-stage support vector machine (SVM) classifier to first predict species from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
180
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 41 publications
(52 reference statements)
3
180
0
Order By: Relevance
“…To improve aerosol corrections in ACORN-5, we iteratively ran the model with different visibilities until the reflectance at 420 nm (which is relatively constant for vegetated pixels) was 1%. Reflectance imagery was corrected for cross-track brightness gradients using a bidirectional reflectance distribution function modeling approach described by Colgan et al (66). The imaging spectrometer data were then orthorectified to the LiDAR digital canopy model.…”
Section: Methodsmentioning
confidence: 99%
“…To improve aerosol corrections in ACORN-5, we iteratively ran the model with different visibilities until the reflectance at 420 nm (which is relatively constant for vegetated pixels) was 1%. Reflectance imagery was corrected for cross-track brightness gradients using a bidirectional reflectance distribution function modeling approach described by Colgan et al (66). The imaging spectrometer data were then orthorectified to the LiDAR digital canopy model.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to vegetation and wetland mapping, hyperspectral data perform high in species mapping and plant invasion applications during the last years (He et al 2011), especially in areas of high habitat and species diversity (Nagendra et al 2013), and are widely employed (Clark and Roberts 2012;Artigas and Pechmann 2010;Féret and Asner 2013;Colgan et al 2012;Hestir et al 2008;Baldeck et al 2014;Ghiyamat et al 2013;Pengra et al 2007;Miao et al 2006;Somers and Asner 2012). Thenkabail et al (2004) demonstrated the use of hyperspectral data by simulating the bands of Hyperion with a hand-held spectroradiometer to discriminate vegetation and agricultural crops.…”
Section: Plant Speciesmentioning
confidence: 99%
“…finer-than the monitored object, to provide an effective tradeoff between within-object and between-object variance (Nagendra 2001). Some of the best performing studies in alien and invasive species detection are based on fine resolution data, either aerial (Dorigo et al 2012;Shouse et al 2013;Artigas and Pechmann 2010;Hantson et al 2012;Clark and Roberts 2012;Colgan et al 2012) or satellite (Laba et al 2008;Walsh et al 2008;Immitzer et al 2012). Dorigo et al (2012) extracted a bi-temporal band ratio (BTBR) and a number of Haralick texture features from bi-seasonal digital orthophotos and successfully detected Fallopia japonica, one of the world's worst invasive alien species, with up to 90.3% PA and 98.1% UA.…”
Section: Plant Speciesmentioning
confidence: 99%
“…almost constant for vegetation) was 1%. The reflectance data were further corrected for cross-track brightness gradients using a bidirectional reflectance distribution function model (Colgan, Baldeck, Féret, & Asner, 2012). Full details on the preprocessing of the VSWIR data can be found in Asner et al (2014) and Colgan et al (2012).…”
Section: Remote Sensing Data and Preprocessingmentioning
confidence: 99%